2003
DOI: 10.1161/01.res.0000097926.29243.96
|View full text |Cite
|
Sign up to set email alerts
|

NHE-1 and NHE-6 Activities

Abstract: T he study 1 published in this issue of Circulation Research showing that a null mutation of NHE-1 improves the tolerance of the heart to ischemia and reperfusion (I/R) is an important contribution for the following reasons: (1) In the animals with null mutation, contracture during the ischemic period was less and ATP levels were preserved compared with wild-type animals. This observation, on the one hand, provides evidence that protection by downregulation of NHE-1 during the ischemic period itself is indeed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Since NHE is also known to be present on the inner mitochondrial membrane (Numata et al 1998) and different NHE inhibitors have been shown to depress the mitochondrial NHE (Cingolani et al 2003), it is likely that mitochondrial function is affected in presence of MIA. It was interesting to note that MIA treatment had no direct effect on mitochondrial respiration or oxidative phosphorylation; however, basal mitochondrial Ca 2+ concentration and Ca 2+ uptake by mitochondria were significantly augmented by treatment with MIA.…”
Section: Discussionmentioning
confidence: 99%
“…Since NHE is also known to be present on the inner mitochondrial membrane (Numata et al 1998) and different NHE inhibitors have been shown to depress the mitochondrial NHE (Cingolani et al 2003), it is likely that mitochondrial function is affected in presence of MIA. It was interesting to note that MIA treatment had no direct effect on mitochondrial respiration or oxidative phosphorylation; however, basal mitochondrial Ca 2+ concentration and Ca 2+ uptake by mitochondria were significantly augmented by treatment with MIA.…”
Section: Discussionmentioning
confidence: 99%
“…The Na + /H + exchanger isoform 1 (NHE1 [SLC9A1]) is the main subtype of membrane proteins that mediate the exchange of one intracellular H + for one extracellular Na + , thereby regulating intracellular pH and cell volume, [21,22] which presented predominantly in the myocardium [23] and is associated with oxidative stress and apoptosis. [24,25] NHE1 is the most abundant subtype of the NHE1 family, and it is expressed in a wide range of tissues, including the heart, kidneys, brain, and gastrointestinal tract. Chronic inhibition of NHE1 reduces heart failure [26][27][28][29] and reduces the production of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of low oxygen supply (which occurs during ischemia/reperfusion [I/R] injury), transporters such as the sodium–hydrogen exchanger (NHE) are important regulators of pHi. 1-3 The NHE1 is the major isoform expressed in heart 3 pharmacologic or genetic inhibition of NHE1 activity and has been proven to protect mouse hearts from I/R injury. 4-7 However, clinical trials using NHE1 in humans showed mixed results and side effects.…”
Section: Introductionmentioning
confidence: 99%